Comparative Study of Thermal Effects on Protein-Enriched Cassava Starch with Snakehead Fish and Mackerel Proteins - Agus Supriadi; Siti Hanggita Rachmawati; Sherly Ridhowati; Gama Dian Nugroho; Daniel Saputra (Green Engineering Society, 2025)
Cassava-starch composites enriched with fish proteins offer a means to tailor texture and moisture management during thermal processing. We evaluated ten formulations (P1–P10) with varying proportions of snakehead fish and mackerel proteins and measured expansion, water absorption, color (ΔE*), and density. Expansion peaked at low protein ratios and subsequently declined: mackerel P2 reached 4.38 ± 0.96%, snakehead P1 reached 4.08 ± 1.40%, and both decreasing to 0.8% at P10. Water absorption also decreased with increasing protein, from 14.04 ± 0.93% (mackerel P1) and 11.67 ± 1.36% (snakehead P1) to 5.54 ± 2.16% and 4.10 ± 0.41% at P10, respectively. The water-absorption-expansion relationship was non-linear and best described by second-order polynomials (Snakehead: y = 0.0764x² − 0.8101x + 2.9686; R² = 0.978 and Mackerel: y = 0.0975x² − 1.4896x + 6.1685; R² = 0.960), indicating diminishing expansion gains at higher absorption. Apparent (saturated) density increased during soaking and plateaued at 150 min; lower-protein formulations exhibited higher saturated density due to greater water uptake. Collectively, these results show that choosing the protein type and ratio enables targeted control of expansion, hydration, and density—mackerel favoring higher expansion at lower absorption, and snakehead providing a more gradual, controllable response—offering practical levers for designing fish-protein–starch products with desired textures.